2011
DOI: 10.6113/jpe.2011.11.6.931
|View full text |Cite
|
Sign up to set email alerts
|

Improved Active Power Filter Performance Based on an Indirect Current Control Technique

Abstract: This paper presents a method for the performance improvement of a shunt active power filter (SAPF) using the indirect current control (ICC) scheme. Compared to the conventional direct current control (DCC) scheme, the ICC gives better performance with a lower number of sensors. A simplified and efficient control algorithm using a low cost Intel 80C196KC microcontroller is implemented using only two current sensors for the source current and one voltage sensor for the DC-link voltage of the SAPF circuit. The ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…In other words, it changes the DCC-based operation to ICC-based operation. Unlike DCC-based operation, ICC-based operation which has been reported in [43][44][45]47] to possess exact information on switching ripples existing in the source current, allows accurate generation of reference currents to continuously control the operation of the SAPF and thus eliminates any unnecessary problem caused by SAPF switching operations.…”
Section: Proposed Simplifications and Refinementsmentioning
confidence: 99%
See 3 more Smart Citations
“…In other words, it changes the DCC-based operation to ICC-based operation. Unlike DCC-based operation, ICC-based operation which has been reported in [43][44][45]47] to possess exact information on switching ripples existing in the source current, allows accurate generation of reference currents to continuously control the operation of the SAPF and thus eliminates any unnecessary problem caused by SAPF switching operations.…”
Section: Proposed Simplifications and Refinementsmentioning
confidence: 99%
“…To date, the conventional STF-pq theory algorithm still produces a non-sinusoidal reference current [7,40,42] and thus forces the SAPF to operate based on a direct current controlled (DCC) scheme [43][44][45]. From previous literature [45][46][47], it is revealed that the SAPF switching operation produces switching ripples which potentially degrade the THD value of the mitigated source current.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the ICC scheme has a simpler control structure which involves a lower number of calculations [31], [34] and can be implemented with a lower number of sensors [30], [34]. As a result, it effectively reduces the system requirements for practical implementation.…”
Section: Introductionmentioning
confidence: 99%